THE ANTIMICROSOMAL AUTOANTIBODIES LEVELS WITH HORMONAL INDICES OF TESTOSTERONE AND PROGESTERONE CONCENTRATION AS MARKER OF PRIMARY INFERTILITY IN (NIGERIAN) WOMEN - Oladimeji, O.S. (European Scientific Journal, ESJ, 2013)
Objective: This study was carried out to determine the anti-microsomal antibodies level, being investigated as one of the marker, as cause of primary infertility in women, along with the serum concentration of the female hormones, such as progesterone and testosterone, to serve as indices. Design: A total of one hundred and twenty (120) Euthyroid female were selected from the volunteers that were recruited, having satisfied the exclusion factor in the designed questionnaire to obtain their informed consents. Thereafter, following the Ethics group recommendations, blood samples were collected from each of the test and control groups. The grouping was designed to contain thirty (30) women each, a week after their menses. Anti-microsomal antibodies (i.e. anti-thyroid peroxidase (anti-TPO)) were determined, using meridian Bioscience Europe anti-TPO assay. Hormonal assay of progesterone, testosterones were determined, using individual hormonal diagnostic ELISA (enzyme linked immuno-sorbent assay) kits. Result / Outcome: The mean concentration of progesterone determined in the pregnant women group among the group that were positive to anti microsomal antibodies was 24.10 + 8.68 ng/ml. This was significantly higher at p<0.05 when compared with the primary infertile women having the concentration of 0.029 + 0.05 ng/ml, whereas the testosterone titer value of the same pregnant women group that were positive to anti-TPO was 5.37 + 4.92 ng / ml, which was significantly lower at P < 0.05, when compared with the testosterone concentration in the primary infertile women group positive to anti-TPO which was 294 + 11.96 ng / ml.